An 18 megapixel 4.3″ 1443 ppi 120 Hz OLED display for wide field of view high acuity head mounted displays. Issue 5 (9th May 2018) - Vieri, Carlin; Lee, Grace; Balram, Nikhil; Jung, Sang Hoon; Yang, Joon Young; Yoon, Soo Young; Kang, In Byeong
Abstract: We developed and fabricated the world's highest resolution (18 megapixel, 1443 ppi) OLED on glass display panel. The design uses a white OLED with color filter structure for high density pixelization and an n‐type LTPS backplane for faster response time than mobile phone displays. A custom high bandwidth driver IC was fabricated. We developed a foveated pixel pipeline appropriate for virtual reality and augmented reality applications, especially mobile systems. Abstract : We developed and fabricated the world's highest resolution (18 megapixel, 1443 ppi) OLED on glass display panel. The design uses a white OLED with color filter structure for high density pixelization and an n‐type LTPS backplane for faster response time than mobile phone displays. We developed a foveated pixel pipeline appropriate for virtual reality and augmented reality applications, especially mobile systems.